2009
DOI: 10.4103/0256-4947.55314
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of male breast carcinoma: 24 years of experience

Abstract: BACKGROUND AND OBJECTIVES:Because breast cancer in men is rare, few patients are available for prospective studies. To learn more about its epidemiology, risk factors, clinical features, genetics and pathology in our country, we conducted a retrospective study of all cases seen in recent decades at our institution.PATIENTS AND METHODS:We identified each case of male breast cancer in the database at the Sher-i-Kashmir Institute of Medical Sciences, Srinagar, Kashmir, India, between the years 1983 to 2007.RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
4
26
0
1
Order By: Relevance
“…The worldwide variation in male breast cancer is similar to breast cancer in women, with higher rates in North America and Europe and lower rates in Asia (5). Rates of male breast cancer in India, Uganda, and Zambia are 5% and 15%, respectively (6,7). These relatively high rates have been attributed to endemic infectious diseases causing liver damage leading to hypoestrogenism (6).…”
Section: To the Editormentioning
confidence: 99%
“…The worldwide variation in male breast cancer is similar to breast cancer in women, with higher rates in North America and Europe and lower rates in Asia (5). Rates of male breast cancer in India, Uganda, and Zambia are 5% and 15%, respectively (6,7). These relatively high rates have been attributed to endemic infectious diseases causing liver damage leading to hypoestrogenism (6).…”
Section: To the Editormentioning
confidence: 99%
“…Chikaraddi et al [2] have reported an incidence rate of 0.4 % of all breast cancer. A study conducted by Rai et al, [12] from North India, revealed the incidence of MBC as 0.5% while Shah et al [13] have reported a relatively high incidence of 4.1% from Kashmir. In our study, the prevalence of MBC in this study was 1.34%, among all MBC cases and 2.50%, among all breast lesion which is similar to the study conducted by Sundriyal et al [14] and Mitra et al [15] The prevalence of MBC increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…Chikaraddi SB et al [5] have reported an incidence rate of 0.4% of all breast cancer. Another study Rai B et al [6] from north india, revealed the incidence of male breast cancer as 0.5% while Shah P et al have reported a relatively high incidence of 2.8% of total resected breast specimen [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Because of its low incidence and rarity of disease the epidemiological data regarding male breast cancer is little as compared to female counterpart. In India only few studies are available regarding incidence, presentation, course and prognosis of male breast cancer [5][6][7] . This study was aimed to analyse incidence and clinical presentation of male breast cancer at regional cancer center of India.…”
Section: Introductionmentioning
confidence: 99%